Understanding the effectiveness of Farm to School programs through food service professionals - Nurse, Gretchen, author; Thilmany-McFadden, Dawn, author; Gunter, Allie, author; Colorado State University, Department of Agricultural and Resource Economics, publisher (Colorado State University. Libraries, 2011)
This study was intended to share perceptions and experiences from the initial years of Colorado Farm to School activities, with a particular focus of the perceived effectiveness of such programs in the eyes of one major stakeholder: the food service staff. Beyond providing a "school-eye view" of the program's impact on employee attitudes and student participation, the evaluation of food service stakeholders in the farm-to-school programs may ultimately lead to the development of 'best practices' for other schools to support their programs.
October 2011.
Keywords: Colorado; student nutrition; public health; farm to school; school cafeterias; farmers